Oral Manifestations in the American Tegumentary Leishmaniasis - da Costa, Daniel Cesar Silva (PLoS One, 2014)
INTRODUCTION: American tegumentary leishmaniasis (ATL) can affect the skin or mucosa (mucocutaneous leishmaniasis – MCL) including the oral cavity. MCL oral lesions are often confused with other oral diseases, delaying diagnosis and specific treatment, and increasing the likelihood of sequelae. Thus, increasing the knowledge of the evolution of ATL oral lesions can facilitate its early diagnosis improving the prognosis of healing. OBJECTIVES: Evaluate the frequency of ATL oral lesion and describe its clinical, laboratory and therapeutic peculiarities. METHODS: A descriptive transversal study was carried out, using data from medical records of 206 patients with MCL examined at the outpatient clinics-IPEC-Fiocruz between 1989 and 2013. Proportions were calculated for the categorical variables and the association among them was assessed by the Pearson's chi-square test. Measures of central tendency and dispersion were used for the continuous variables and their differences were assessed by both parametric (t test) and non parametric (Mann-Whitney) tests. P-values <0.05 were considered as significant. RESULTS: The most affected site was the nose, followed by the mouth, pharynx and larynx. Seventy eight (37.9%) have oral lesions and the disease presented a lower median of the evolution time than in other mucous sites as well as an increased time to heal. The presence of oral lesion was associated with: the presence of lesions in the other three mucosal sites; a smaller median of the leishmanin skin test values; a longer healing time of the mucosal lesions; a higher recurrence frequency; and a smaller frequency of treatment finishing and healing. When the oral lesion was isolated, it was associated with an age 20 years lower than when the oral lesion was associated with other mucosal sites. CONCLUSION: Considering the worst therapy results associated with the presence of oral lesions, we suggest that lesions in this location represent a factor of worse prognosis for MCL.